The sociolinguistic problems of English medium instruction in the Middle East and North Africa: Implications for epistemic access - Ntombela, Berrington Xolani Siphosakhe (Frontiers in Psychology, 2023)
The global spread and dominance of English in higher education has reached alarming heights. While there has been a drive to argue for the relevance and importance of education through local languages, English has snatched the biggest slice of the cake by subtly imposing itself as the sole global language of education. This paper interrogates the sociolinguistic problems posed by the hegemony of English language. It argues that globalization and internationalization work in tandem with neo-colonial and neoliberal operations to create a class of global citizens that must support the economic aspirations of English imperial expansion and sustenance. The arguments are drawn from the experiences of Middle East and North Africa as well as lessons from Eastern and Southern Africa. The paper adopts a critical approach in order to place urgency against the onslaught of English medium of instruction in global higher education. This is done by problematizing the rhetoric of globalized and internationalized education. The paper then draws conclusions on epistemic access in the context of burgeoning knowledge economies. It argues that English medium of instruction is implicated in stalling access to knowledge for the great majority in order to cater for and safeguard the economic dominance of the elite minority.